Preliminary Analysis of Yeast Communities Associated with the Spontaneous Fermentation of Musalais, a Traditional Alcoholic Beverage of Southern Xinjiang, China - Lixia, Z.; Mingfu, G.; Dongqi, G.; Christensen, M.; Xujie, H.; Hongmei, L.; Yingge, F.; Shu, F. (South African Journal of Enology and Viticulture, 2016)
Musalais is a traditional alcoholic beverage made by the Uighur people in southern Xinjiang, China. The initial fermentation juice is obtained by prolonged boiling of local grape juice and grape residues. In the current study, 242 yeast isolates were obtained from 18 samples (grapes, derived starting products, and progressive stages of fermentation), and 20 phenotypes were distinguished, based on colony characteristics on WL nutrient agar. Fifty representative isolates were selected and found to belong to eight genera (based on rRNA gene sequence analysis). Among the non-Saccharomyces species present on the grapes and related derived substrates, Hanseniaspora spp. was the dominant species. However, nearly all of these species were absent in early fermentation. Saccharomyces cerevisiae was not found until the onset of spontaneous fermentation and quickly became the dominant species. The identified yeast community could be used to further develop indigenous yeast strains to serve the traditional technology of Musalais. The production of Musalais, from a starting substrate that has been boiled for 15 hours to kill all, or nearly all, yeast cells, provides fresh insights into the production of ethanol by the fermentation of grape juice.